COVID-19 Pandemic and its Effect on Mental Health among General Population of Gandaki Province - Shrestha, Sandhya; Gurung, Bandi; Gaire, Bipula; Gurung, Tsewang Palmo; Shahi, Nikita (Journal of College of Medical Sciences-Nepal, 2022)
Introduction: Mental health problem is the big issues during Covid 19 pandemic so this study aims to explore the impact of COVID-19 pandemic on the mental health among general population of Gandaki province Methods: An Analytical cross sectional study was conducted from Nov/Dec 2021among 168 general population above 18 years of age.Nepali version of self reporting DASS 21 scale was used for data collection. Data was analyzed using SPSS 19.0 version. Descriptive statistics and inferential statistics chisquare & bivariate logistic regression was used for data analysis Results: Among the participants 29.8% had depression, 26.8% had anxiety and 16.1% had stress in varying severity from mild to extremely severe forms. There was signification association between depression and religion, marital status and educational status and there was association between anxiety and stress with marital status and occupation but there is no significant with other demographic variables. Bivariant regression models revealed unmarried respondents were 2.6 times more likely to have depressive symptoms, below Graduation educational status were 3 times more likely to have depressive symptoms. Unmarried respondents were 2.4 times more likely to have anxiety, in the same way unmarried respondents were 5 times more likely to have stress at 95 % CI i.e. pvalve <0.05. Conclusions: More than one fourth respondents was having depressive symptoms, anxious and near to one fifth was stressed so there should be increasing public awareness of mental health and coping strategies is essential to promote mental health to the general population of Gandaki province. Keywords: COVID-19; pandemic; mental health; general population.